9th International conference on biosience, biochemistry & bioinformatics 2018 - Keng, Wong Kah (Pusat Pengajian Perubatan, 2019)
Transient receptor potential cation channel subfamily M member 4 (TRPM4) is overexpressed in activated B-cell-like subtype of diffuse large B-cell lymphoma (ABC-DLBCL) associated with poor survival. In this study, its functions in the disease and the potency of its inhibitor 9-phenanthrol were investigated. The biological functions associated with TR.PM4 mRNA expression were examined through Gene Set Enrichment Analysis (GSEA) in ABC-DLBCL cases (n=15). The cytotoxicity of 9-phenanthrol in three ABC-DLBCL cell lines (SUDHL2, OCI-LY3, OCI-LYIO) was tested at six different concentrations (0.0InM, 0.1 nM, InM, lOnM, 25nM, 50nM). GSEA results showed that cell cycle gene sets conferred the highest number of gene sets representing 42% (n=21/50) of the top 50 most significantly enriched gene sets ranked according to false discovery rate (FDR; all 50 gene sets had FDRO.OI), followed by DNA replication (n=8/50; 16%) and RNA processing (n=8/50; 16%), suggesting the roles of TRPM4 in cell cycle progression and cellular division of ABC-DLBCL. In terms of the cytotoxicity effects of 9-phenanthrol, the resulting GI50 for all ABC-DLBCL cell lines ranged from 19nM-41,88nM. In conclusion, TRPM4 is potentially involved in the cell cycle progression and cellular division of ABC-DLBCL cells, and the TRPM4 inhibitor 9-phenanthrol was cytotoxic against ABC-DLBCL cells.